Societal Altmetrics Impact of Research Publication on Academia and ResearchGate: Scientometric Citation Analysis - V Thangavel (Nur Science Institute, 2026)
Social websites serve as a unique, quick, and sometimes early indicator of research visibility that supplements conventional citation measures, according to a comparative scientometric examination of the societal impact of research articles on social websites (typically evaluated using Altmetrics). Social impact gauges instant attention, engagement, and reach among the public, policymakers, and other researchers, whereas academic influence is determined by long-term citations. Research and Review articles typically reach a wider audience in the professional or public sphere, as evidenced by their better social impact (higher Altmetrics scores) compared to original research publications. In this study, researchers examined the various social effects of research platforms, i.e., Academia and ResearchGate. This study's goal is to investigate how websites could provide these services for handling research data and integrating all networks to provide the data. The significance of distributing and preserving research data and daily citations is monitored by their respective geographical areas, views of citation, styles of access, utilisation of time, Countries, Cities, Universities, and the title of the research. Jobs, reading pages, and search engines are used for downloads and views. Many users use ResearchGate for the dissemination of their research works. But compared to other research websites, the Academia webpage is very important and user-friendly, keeping user data in a multidimensional view and tracing out their details at any time. The researchers advised everyone to benefit from Academia and keep their research data in Academia for more advantages in future endeavours. It shows that most of the users are going to use the Academia website to keep their research records in Academia in future because of the continuous development and enhancements in this search engine. ResearchGate is a free and well-established platform for researchers; everyone can benefit from it.